2009
DOI: 10.1186/1471-2407-9-376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical meaning of age-related expression of fecal cytokeratin 19 in colorectal malignancy

Abstract: BackgroundColorectal cancer (CRC) is one of the leading causes of malignant death worldwide. Because young age of onset is often considered a poor prognostic factor for CRC, it is important to identify the poor outcomes of CRC in a younger population and to consider an aggressive approach by implementing early treatment. Our aim was to specifically quantify the fecal cytokeratin 19 (CK19) transcript from CRC patients and investigate its correlation with clinical stage, tumor malignancy, and age.MethodsThe quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In the case of chymotrypsin C suppression, cytokeratin 18, keratin 19, and prolyl 4-hydroxylase were upregulated 1.31, 1.28, and 1.55 folds, respectively, whereas lamin A/C and heat shock 70 kDa protein 8 were downregulated to about 60 or 79%, respectively. All of these differentially expressed proteins have been reported to be involved in cancer metastasis [12][13][14][15][16][17][18][19][20][21][22][23]. Although the above proteins are all associated with cancer, they (with the exception of cytokeratin 18) had no close correlation with either upregulation or suppression of chymotrypsin C. The changes at protein levels of cytokeratin 18 were also consistent with its mRNA level, which was verified by quantitative RT-PCR.…”
Section: Chymotrypsin C and Related Proteins Involved In The Aspc-1 Csupporting
confidence: 58%
“…In the case of chymotrypsin C suppression, cytokeratin 18, keratin 19, and prolyl 4-hydroxylase were upregulated 1.31, 1.28, and 1.55 folds, respectively, whereas lamin A/C and heat shock 70 kDa protein 8 were downregulated to about 60 or 79%, respectively. All of these differentially expressed proteins have been reported to be involved in cancer metastasis [12][13][14][15][16][17][18][19][20][21][22][23]. Although the above proteins are all associated with cancer, they (with the exception of cytokeratin 18) had no close correlation with either upregulation or suppression of chymotrypsin C. The changes at protein levels of cytokeratin 18 were also consistent with its mRNA level, which was verified by quantitative RT-PCR.…”
Section: Chymotrypsin C and Related Proteins Involved In The Aspc-1 Csupporting
confidence: 58%
“…It is a protein that in humans is encoded by the KRT19 gene [24,25]. Its expression can be observed in many normal tissues, and it is overexpressed in lung cancer, colorectal cancer and breast cancer [26-29]. SCC-Ag is a sub-fraction of the tumor antigen TA-4, a 48 kDa glycoprotein first isolated by Kato and Torigoe [30].…”
Section: Discussionmentioning
confidence: 99%
“…Cyfra21-1 is a small molecular protein responsible for structural integrity of epithelial cells, which also functions to promote cell growth, adhesion, migration and invasion [34]. High Cyfra21-1 serum titers have been demonstrated to correspond to poor prognosis in patients with non small cell lung cancer and colorectal cancer [21,26,33]. SCC-Ag may be involved in the malignant behavior of squamous cell cancers, functioning in invasion and/or metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…(16)(17)(18) Together, these studies indicate that newly formed lymphatic vessels are likely to be the major pathway for the spread of tumors to the PNP.In the present study, we used cytokeratin 19 (CK19), (19) a commonly used prognostic marker, to evaluate lymphatic invasion. It has been reported that CK19 is highly expressed in lymph nodes exhibiting disseminated tumor cells, (20) and significant levels of CK19 have been found in the peripheral blood of patients with other malignancies, including liver, breast, and pancreatic cancers. (21,22) Thus, using CK19 as a potential marker for lymphatic invasion of the PNP may both clarify the significance of lymphangiogenesis as a major route for the spread of tumor cells to the nervous system and provide mechanistic information regarding this method of tumor metastasis for further research and clinical application.…”
mentioning
confidence: 99%